Normal Evoked Response to Rapid Sequences of Tactile Pulses in Autism Spectrum Disorders - Ganesan, Santosh; Khan, Sheraz; Garel, Keri-Lee A.; Hämäläinen, Matti S.; Kenet, Tal (Frontiers in Human Neuroscience, 2016)
Autism spectrum disorder (ASD) is a developmental disorder diagnosed behaviorally, with many documented neurophysiological abnormalities in cortical response properties. While abnormal sensory processing is not considered core to the disorder, most ASD individuals report sensory processing abnormalities. Yet, the neurophysiological correlates of these abnormalities have not been fully mapped. In the auditory domain, studies have shown that cortical responses in the early auditory cortex in ASD are abnormal in multiple ways. In particular, it has been shown that individuals with ASD who were also language impaired, have abnormal cortical auditory evoked responses to rapid, but not slow, sequences of tones. Here, we tested the somatosensory domain in ASD for abnormalities in rapid processing of tactile pulses, to determine whether abnormalities there parallel those observed in the auditory domain. Specifically, we tested the somatosensory cortex response to a sequence of two tactile pulses with different (short and long) temporal separation. We analyzed the responses in cortical space, in primary somatosensory cortex. As expected, we found no group difference in the evoked response to pulses with long temporal separation. Contrary to findings in the auditory domain and to our hypothesis, we also found no group differences in the evoked responses to the sequence with a short temporal separation. These results suggest that rapid temporal processing deficits in ASD are not generalized across multiple sensory domains, and are unlikely to underlie the behavioral somatosensory abnormalities observed in ASD.